Implementation of Flashcard Media in Improving Student Learning outcomes Through Vocabulary - Opik Ali Rohman; Yuni, Yuni Setiawati (Universitas Muhammadiyah Kuningan, 2024)
This study examines the effectiveness of the application of Flashcard media to improve studenst achievment in grade II at Babakanmulya 1 Public Elementary School. To determine the effect of applying Flashcard media on student achievment in English lessons with the theme of Family is the aim of this study. Researchers used the Quantitative method in the form of the One Group Pre-Test Post-Test Experiment. In this study, it was conducted using a sample of all grade II students at SDN 1 Babakanmulya as many as 9 people. The results of this study reveal that the application of Flashcard media in the learning process can increase student learning outcomes through vocabulary mastery. The authenticity of these statements can be tested through evaluation results before the application of Flashcard media in the learning process. The average score is 62, in contrast to the evaluation results after using Flashcard media in learning, the average score is 81. In addition, the use of Flashcard media also makes learning more conducive and interactive.